Assessing the resilience of rural tourism in Indonesia during and after the Covid-19 pandemic using the multimoora method - Nafiah Ariyani; Akhmad Fauzi (Amfiteatru Economic, 2024)
Tourism villages play a vital role in developing rural areas in Indonesia. However, they are vulnerable to external shocks, including economic fluctuations and recent public health events like the COVID-19 pandemic. This study analyses the resilience of 24 tourism village destinations in Indonesia from 2019 to 2022. The MULTIMOORA method (multi-objective optimisation by ratio analysis plus the full multiplicative form) was employed to assess resilience. The findings indicate that most tourism villages in Indonesia experienced significant impacts during the initial year of the pandemic. However, they demonstrated the ability to recover, as evidenced by changes in their rankings before and after the pandemic. This result suggests that tourism villages in Indonesia show strong capacity and performance to rebound from pandemic-related shocks. The novelty of this research lies in its ability to provide a comprehensive and timely assessment of the resilience of tourism villages in Indonesia during the COVID-19 pandemic, utilising a robust methodological approach and offering valuable insights into their capacity to recover from external shocks. The research significantly contributes to the broader literature on tourism village resilience. It provides empirical evidence, methodological innovation, and valuable insights into the economic resilience of the sector in the face of external shocks. The findings have implications for policymakers, researchers, and practitioners working in tourism development.
Keywords: R58; Z32; Z38; 330; rural tourism resilience; pandemic shock; Multimoora; rural development